Mối quan hệ giữa các tác nhân của thực thi Logistics ngược và kết quả kinh tế: Nghiên cứu thực nghiệm cho lĩnh vực kinh doanh bán lẻ hàng điện tử tại thành phố Đà Nẵng, Việt Nam - Nguyễn Huy, Tuân; Lê Tấn, Bửu (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2020)
This study focuses on considering the relationship between the antecedents of reverse Logistics implementation and economic performance of electronic retail businesses. By combining qualitative and quantitative research methods, the results were found in this study including: (i) Corporate reputation was discovered as a new factor, therefore, the relationship between corporate reputation with reverse logistics implementation and between corporate reputation and resource commitment are both detected in the context of reverse logistics; (ii) Reverse Logistics implementation not only has a significant direct impact on economic performance but also plays an intermediary role in the indirect impact relationships among information technology capability, corporate reputation and economic performance; and (iii) The empirical research showed that except that there is no basis to conclude that the resource commitment has a positive impact on the reverse logistics implementation, all the remaining six hypotheses are accepted. Some research implications have given in order to help electronic retail businesses to comprehend and develop well the antecedents of reverse logistics implementation contributing to improving economic performance in business operations.
Keywords: Reverse Logistics implementation; Resource commitment; Corporate reputation; Economic performance; Information technology capability